Bahasa Sunda Sudah di Ambang Pintu Kematiankah? - Sobarna, Cece (Makara Human Behavior Studies in Asia, 2007)
The death of a language becomes very popular issue recently all over the world and it is included Sundanese language. This has something to do with the phenomenon which was happened in West Java, especially Bandung, where most of the people, especially young generation are assumed becoming reluctant to use Sundanese language in their daily conversation. This tendency is interesting to be analyzed from the language death point of view. Because of that reason, we need comphrehensive strategic efforts to maintain Sundanese language from extinction.